(untitled) (Research, Society and Development, 2023)
Psychomotricity can be defined as a science that presents the connection between the psychic and the movement, favoring the development of the motor, affective, cognitive and social aspects. Psychomotor work in early childhood education is relevant, as the child is in a stage of discovery, of himself and the world around him. Based on this premise, this study aimed to review the literature, from 2015 to 2021, on the relationship between psychomotricity and early childhood education. The data search was carried out in the Google Scholar, Periodical Capes and Scielo databases, yielding 962 titles, and of these, 9 met the inclusion criteria and were reviewed. It was found that psychomotricity is part of the integral development of the child, and when well worked, it serves as a bridge to the learning of reading and writing. Therefore, it is essential that the teacher be a stimulator in the psychomotor work of children, getting involved with the subject, with the particularities of each one, and planning their work with a comprehensiveness of all the basic psychomotor factors.